Multimodality imaging to identify lipid-rich coronary plaques and predict periprocedural myocardial injury: Association between near-infrared spectroscopy and coronary computed tomography angiography - Ota, Hideaki; Matsuo, Hitoshi; Imai, Shunsuke; Nakashima, Yuki; Kawase, Yoshiaki; Okubo, Munenori; Takahashi, Hiroshi; Kawai, Hideki; Sobue, Yoshihiro; Kawasaki, Masanori; Kondo, Takeshi; Muramatsu, Takashi; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background This study compares the efficacy of coronary computed tomography angiography (CCTA) and near-infrared spectroscopy intravascular ultrasound (NIRS–IVUS) in patients with significant coronary stenosis for predicting periprocedural myocardial injury during percutaneous coronary intervention (PCI). Methods We prospectively enrolled 107 patients who underwent CCTA before PCI and performed NIRS–IVUS during PCI. Based on the maximal lipid core burden index for any 4-mm longitudinal segments (maxLCBI4mm) in the culprit lesion, we divided the patients into two groups: lipid-rich plaque (LRP) group (maxLCBI4mm ≥ 400; n = 48) and no-LRP group (maxLCBI4mm < 400; n = 59). Periprocedural myocardial injury was a postprocedural cardiac troponin T (cTnT) elevation of ≥5 times the upper limit of normal. Results The LRP group had a significantly higher cTnT (p = 0.026), lower CT density (p < 0.001), larger percentage atheroma volume (PAV) by NIRS–IVUS (p = 0.036), and larger remodeling index measured by both CCTA (p = 0.020) and NIRS–IVUS (p < 0.001). A significant negative linear correlation was found between maxLCBI4mm and CT density (rho = −0.552, p < 0.001). Multivariable logistic regression analysis identified maxLCBI4mm [odds ratio (OR): 1.006, p = 0.003] and PAV (OR: 1.125, p = 0.014) as independent predictors of periprocedural myocardial injury, while CT density was not an independent predictor (OR: 0.991, p = 0.22). Conclusion CCTA and NIRS–IVUS correlated well to identify LRP in culprit lesions. However, NIRS–IVUS was more competent in predicting the risk of periprocedural myocardial injury.